Quantifying blistering on Vajrasana pagoda using complementary in-situ non-destructive techniques - Yao Zhang; Bo Li; Ziyi Cai; Hong Guo; Xiang He (Humanities & Social Sciences Communications)
Abstract Blistering is a common yet under-quantified form of decay in historic stonework, progressively causing surface spalling and threatening structural integrity. Current in-situ surveys often rely on a single investigative technique and therefore miss either early-stage subsurface instabilities or precise surface metrics. This study employed a complementary approach combining field observations with infrared thermography (IRT) and three-dimensional laser scanning to examine the blistering on the Vajrasana pagoda at Miaozhan Temple, built in 1458 during the Ming dynasty. Time-sequenced thermograms captured thermal dynamics, and principal component thermography (PCT) sharpened blistering boundaries, exposing incipient delamination. The laser scans, acquired at 0.204 mm point spacing, yielded detailed morphology and enabled direct calculation of blistering area, volume, and deformation height. Fusing the thermal data with the 3D mesh produced a thermographic model that visualizes both heat anomalies and surface protrusions. Finite element modeling (FEM) derived from this mesh predicted stress concentrations along the blister upper edges, identifying zones most prone to fracture. The data from both methods were consistent and complementary, providing a comprehensive foundation for the preservation and restoration of the Vajrasana pagoda.